Pain management practice and associated factors among nurses working in Ethiopia: A systematic review and meta-analysis - Melesse Abiye Munie; Amsalu Baylie Taye; Befkad Derese Tilahun; Addis Wondmagegn Alamaw; Gebremeskel Kibret Abebe; Migbaru Endawoke Tiruye; Biruk Beletew Abate (PLoS ONE, 2025)
Background Pain management is a crucial component of patient care that promotes relaxation, lowers complications, improves quality of life, and shortens hospital stays. Several studies assessed the nurses’ pain management practices in Ethiopia. However, the findings of these studies are highly variable and inconsistent. Therefore, the study aims to determine the overall prevalence of pain management practice and associated factors among nurses working in Ethiopia. Method The study included all observational quantitative research articles conducted among nurses in Ethiopia. We used Google Scholar, PubMed, Cochrane Library, and Scopus searching databases. The Newcastle—Ottawa Scale was used to check the study quality. Then I2 statistics and Cochran’s Q test were used to evaluate heterogeneity. The Funnel, Egger’s test, and non-parametric trim and fill effect tests were used to check publication bias by using a random effect model. Finally, we conducted subgroup analysis and sensitivity tests to evaluate statistical heterogeneity and the presence or absence of any influential study. Result In the final analysis, we included eighteen studies, and 4,213 nurses participated. The overall pooled prevalence of nurses with good pain management practice was 43.79% (95% CI: 38.52, 49.06%). In-service training AOR; 95% CI 3.21 (1.87, 4.54), good knowledge AOR; 95% CI 2.44 (1.78, 3.09), positive attitudes AOR; 95% CI 2.84 (1.24, 4.44), and pain management guidelines in health facilities AOR; 95% CI 3.46 (1.48, 5.44) were the significant associated factors with pain management practice among nurses in Ethiopia. Conclusion This study found that over half of Ethiopian nurses had poor pain management practices. Knowledge, attitude, training, and pain management guidelines in health facilities were significant factors. Therefore, health managers and stakeholders should prioritize pain management awareness, attitudes, availability of guidelines, and in-service training to improve patient care and outcomes.